Keywords for children's literature - Nel, Philip, 1969-; Paul, Lissa; Christensen, Nina, 1968- (New York : New York University Press, 2021)
"This title is a second edition of the "Keywords for Children's Literature." This work provides a list of essential terms for the study of children's literature with a discussion of each term"--
Includes bibliographical references and index.
Keywords: Children's literature -- History and criticism -- Terminology